فاعلية الخرائط الذهنية الالكترونية باستخدام السبورة الذكية في الادراك البنائي لدى طلاب الصف الثاني المتوسط لمادة الفيزياء - كطفان الشون ا.د. هادي; ماضي م.م.مصطفى لفته (Journal of College of Education, 2021)
The research aims to identify Effectiveness of Electronic mind mapping strategy by using smart board in constructive perception with intermediate schools second year students of Physics , For realization of this research the experiment carried out on intermediate schools second year students of Hurr Riyahi School as sample for research and randomly 27 intermediate and high schools of Educational directorate of Diwaniyah province were selected including computer lab and smart board, the research sample contains on (54) students, (27) students in each group and both groups are equal, to prove the research hypothesis both scholars prepared constructive perception scale towards physics subject (33 passage) it was realized by their faithfulness, realization and application after end of experiment, the results led to a statistical significant difference between intermediate grades constructive perception scale towards physics between experimental group students and blank group students and experimental group students. In the light of research results both scholars concluded the Effectiveness of Electronic mind mapping in teaching physics methods with intermediate second year students.